RESEARCH OF WOUND HEALING EFFECT OF PHYTOMINERALSORBENT ON THE BASIS OF MONTMORILLONITE - Ulyana Krut; Andrey Shaposhnikov; Mikhail Korokin (Belgorod National Research University, 2017)
Introduction: The results of preclinical investigation of the wound healing effect of phytomineralsorbent (PMS) based on montmorillonite are presented. Objectives: Study of the possibilities of pharmacological correction of purulent wound process with the help of various medicinal forms of phytomineral sorbent based on montmorillonite. Methods: Purulent wounds were modeled in white rats of the Wistar line in the interblade area 3 cm2. Wound dressing was performed daily for 21 days by PMS in the form of powder and gel, and also by the comparison preparation Dexpanthenol (Russia, Pharmstandard). The wound healing effect was carried out according to morphological parameters of histological sections, clinical and biochemical parameters of blood and exudate of the animals under study. Results and discussion: The wound defect of rats, the ligation of which was carried out by phytomineral sorbents, was significantly less than the control 2 times, the depth of necrosis in the acute phase of the wound process was up to 0.85 microns deep, which is 1.7 times less than in the control group. The use of Dexpanthenol in the acute stage was characterized by a suppuration reaction and the presence of microbes. When studying the dynamics of the most important rat blood parameters during wound healing, it was established that the content of immature neutrophils in the regeneration phase in animals using PMS in the form of powder was lower by a factor of 2 compared to the control group and group of animals using the drug Dexpanthenol; the concentration of the total protein in the blood of animals in experimental groups with the use of the preparation Dexpanthenol and PMS based on montmorillonite in the forms of powder and gel were significantly lower than the control one by 18-25% on the third day of the experiment. Exudation of purulent wounds of animals, wound dressings which were performed by PMS in the form of powder, ceased on the second day, the remaining animals lasted up to 5 days. Conclusion: PMS in the form of powder has best effect of wound healing on inflammatory stage of injury.